The 'sliding sign' in conjunction with sonovaginography: is this the optimal approach for the diagnosis of Pouch of Douglas obliteration and posterior compartment deep infiltrating endometriosis?. Issue 3 (August 2013) - Menakaya, Uche; Reid, Shannon; Infante, Fernando; Condous, George
Abstract: Introduction : Endometriosis is a chronic peritoneal disease that may progress as a deep infiltrating lesion involving the posterior compartment of the pelvis. Efforts to improve pre‐operative knowledge of the location and extent of these lesions have resulted in the development of Transvaginal ultrasound (TVS) as the first‐line imaging modality for extra‐ovarian endometriosis. However, various techniques of TVS have been described in the literature for this purpose. Methods : In this review we will detail the evolution of TVS as the primary imaging modality in the pre‐operative diagnosis of posterior compartment deep infiltrating endometriosis (DIE). We will also discuss the potential of an emerging new real‐time diagnostic ultrasound‐based technique known as the 'sliding sign' in combination with office gel sonovaginography for the pre‐operative diagnosis of Pouch of Douglas obliteration and posterior compartment DIE. Conclusion : Implementation of the new real‐time dynamic, reproducible and simple 'sliding sign' in conjunction with SVG has the potential to challenge the current concept that traditional laparoscopy is the 'gold standard' modality for the diagnosis of women with posterior compartment DIE.